The Place and the Role of Civic Education in the Republic of Macedonia - Trajkovski, Ilo (Sowi-online e.V., 2003)
Against the general trend, the author critically concludes that the Macedonian educational authorities at the time did not have clear ideas and orientation towards civic education. They were moving back and forth. Today, the situation is different. Although not yet well institutionalized, the idea of civic education is already accepted and introduced as a new paradigm in social education.
Keywords: civic education, citizenship, Republic of Macedonia